2022
DOI: 10.3390/children9081256
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Tissue Cryopreservation in Children and Adolescents

Abstract: Cancer during childhood and adolescence remains a major public health issue, affecting a significant portion of this age group. Although newer anti-cancer treatments have improved survival rates, this comes at a cost in terms of gonadotoxic effects. As a result, the preservation of fertility is important. Ovarian tissue cryopreservation, one of the newest methods, has some advantages, especially for prepubertal patients: no need for ovarian stimulation, thus, no further risk for estrogen-sensitive cancer types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 109 publications
0
5
0
Order By: Relevance
“…Apart from these factors, the age of the patient at the time of chemotherapy also has great impact on the return of menstruation and ovulation, with more favorable results being reported in younger patients (ESMO 2018) [ 9 , 51 , 52 ]. Taking all the above into consideration, it is evident that oocyte cryopreservation is an option that should be offered to all patients scheduled to receive chemotherapy, either by ovulation induction and oocyte aspiration prior to the beginning of treatment or by controlled ovarian hyperstimulation followed by oocyte cryopreservation 12 months after the end of chemotherapy (ESMO 2018) [ 9 , 53 , 54 ]. While ovarian stimulation is a safe choice for patients with GCTs, it is permitted only for stage IA granulosa-type SCSTs and after discussion in a multidisciplinary board, while it is contraindicated for stages > IA, in which other fertility preservation techniques that do not require ovarian stimulation should be applied (Centres Experts TMRG 2022) [ 24 ].…”
Section: General Principles Of Therapeutic Managementmentioning
confidence: 99%
“…Apart from these factors, the age of the patient at the time of chemotherapy also has great impact on the return of menstruation and ovulation, with more favorable results being reported in younger patients (ESMO 2018) [ 9 , 51 , 52 ]. Taking all the above into consideration, it is evident that oocyte cryopreservation is an option that should be offered to all patients scheduled to receive chemotherapy, either by ovulation induction and oocyte aspiration prior to the beginning of treatment or by controlled ovarian hyperstimulation followed by oocyte cryopreservation 12 months after the end of chemotherapy (ESMO 2018) [ 9 , 53 , 54 ]. While ovarian stimulation is a safe choice for patients with GCTs, it is permitted only for stage IA granulosa-type SCSTs and after discussion in a multidisciplinary board, while it is contraindicated for stages > IA, in which other fertility preservation techniques that do not require ovarian stimulation should be applied (Centres Experts TMRG 2022) [ 24 ].…”
Section: General Principles Of Therapeutic Managementmentioning
confidence: 99%
“…Re-implantation of ovarian cortex tissues can preserve not only fertility but also a normal hormonal milieu that may yield other health benefits such as improved bone and cardiovascular health and sexual function. This approach has resulted in pregnancy rates of approximately 30% and endocrine recovery in >90% of women [Fabbri et al, 2022;Arapaki et al, 2022;Dolmans et al, 2021].…”
Section: Groupmentioning
confidence: 99%
“…Porcu et al reported the first birth of healthy twins in a patient who underwent bilateral oophorectomy for ovarian cancer and was pregnant with her own cryopreserved oocytes [131]. Besides, 131 pregnancies and 75 live births (expected to exceed 200 by 2020) have been reported after slow freezing and transplantation, whereas only 4 deliveries have been described after vitrification [132].…”
Section: Ovarian Tissue Cryopreservationmentioning
confidence: 99%